Post-Suharto’s Jabotabek region: new issues of demographic and socio-economic change in western java - Günter Spreitzhofer, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
The future development of Western Java is intimately linked to the growth of its metropolitan region Jabotabek, the mega-urban agglomeration around Indonesia’s capital Jakarta. This article deals with theinterdependence of economic, spatial and demographic change within Metro-Jakarta, South-East Asia's most densely populated urban region. Focus has been put on aspects of urban living conditions and the dynamic city-development of the late 1990s, which has been politically pushed since the beginning of Suharto’s pro-western ‘New Order’ in the late 1960s. The deregulation packages of the past decade have resulted in enormous international capital influx, the creation of new towns and an increasing transformation of sectoral employment, which cannot be controlled successfully by regional and local authorities. This is due to the dominance of private, partly international developers, whose interest in globalizing low-wage Jabotabek is footloose in character and at present limited due to Indonesia’s economic and political turmoil. All this will postpone Jabotabek’s rise to the stature of a global region